2007
DOI: 10.1111/j.1525-1438.2007.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating neutrophils may play a role in the host response in cervical cancer

Abstract: Neutrophil migration is a key event in the inflammatory response of any origin, and neutrophils may present antitumor activity. We investigated the number and function of circulating neutrophils obtained from patients with cervical neoplasia at different stages. Patients with preinvasive (cervical intraepithelial neoplasia, CIN3, n= 6) or microinvasive ([MICRO] stage IA1, n= 4) neoplasia were evaluated together as CIN/MICRO group (n= 10), while patients at stages II-IV were evaluated as invasive group (INV, n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 31 publications
2
34
0
1
Order By: Relevance
“…In cervical cancer, elevated neutrophil counts, fewer lymphocytes, or high NLR have proved to be significantly predictive of survival. 10,13,19,30,31 Whereas Wang et al 32 failed to demonstrate the value of pretreatment NLR in predicting survival of patients subjected Lee et al 10 also analyzed the prognostic value of NLR in 1,061 patients with cervical cancer (early stage, 82%) who were variably treated and followed for a median of 53 months. Patients with higher NLR were younger and had more advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…In cervical cancer, elevated neutrophil counts, fewer lymphocytes, or high NLR have proved to be significantly predictive of survival. 10,13,19,30,31 Whereas Wang et al 32 failed to demonstrate the value of pretreatment NLR in predicting survival of patients subjected Lee et al 10 also analyzed the prognostic value of NLR in 1,061 patients with cervical cancer (early stage, 82%) who were variably treated and followed for a median of 53 months. Patients with higher NLR were younger and had more advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…These studies include colorectal cancer, 12 gastric cancer treated with FOLFOX chemotherapy 10 or neoadjuvant chemotherapy, 13 and small hepatocellular carcinoma undergoing radiofrequency ablation. 14 In cervical cancer, some reports showed that low circulating lymphocytes, 15 elevated levels of neutrophil counts, 16 or high pretreatment NLR 17 is a risk indicator for prognosis. However, Wang et al 18 found that pretreatment NLR and PLR failed to predict the survival of patients with cervical cancer treated with neoadjuvant chemotherapy and radical hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been observed that persistent infection with a higher likelihood of progression to high-grade lesions and invasive carcinoma can occur in the face of an ineffective immune response. In this context and considering that HPV infection is restricted to epithelial cells, the importance of the local immune response is highlighted, making the components present in the microenvironment crucial for lesion development or regression [33][34][35][36] . The role of GITR has been unclear until now, emphasizing the importance of the present study to clarify the immune response in the cervical microenvironment.…”
Section: Ethical Considerationsmentioning
confidence: 99%